Experimenting CORE learning model on the students’ problem-solving skills based on their emotional intelligence - Sutopo, Sutopo; Yumna, Janika Salma; Kuswardi, Yemi (Universitas Ahmad Dahlan, 2024)
In this study, we aim: (1) to find out which learning model resulted in the better problem-solving skills—the CORE learning model with putar bawah game and labyrinth board game or the direct teaching; (2) to find out which levels of emotional intelligence resulted in better problem-solving skills—high, intermediate, or low emotional intelligence; (3) to find out the interaction between the learning models and the students’ emotional intelligence. This research was a quasi-experimental research which involved the VIII-grade students of SMP Negeri 5 Surakarta in the 2022/2023 academic year. The samples used were two classes taken by cluster random sampling. The data collection techniques used were documentation, tests, and questionaires. The data analysis technique used two-way analysis of variance with unequal sample sizes. Based on the results of the analysis, we conclude that: (1) the CORE model with putar bawah game and labyrinth board game media resulted in the better problem-solving skills than the direct teaching; (2) students with higher emotional intelligence had better problem-solving skills than lower emotional intelligence; (3) there is no interaction between the learning model and the students’ emotional intelligence.